Pengaruh Model Discovery Learning Berbantuan Liveworksheets Terhadap Berpikir Kritis dan Efikasi Diri - Ni Wayan Intan Permatasari; I Wayan Santyasa; Ketut Agustini; Ni Nyoman Parwati; I Komang Sudarma (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Critical thinking skills and self-efficacy play a crucial role in mathematics learning; however, both remain relatively low due to the dominance of conventional methods and the limited use of technology. This study aims to analyze the effect of Discovery Learning with Liveworksheets (DLLW), Discovery Learning (DL), and Direct Instruction (DI), while controlling for prior knowledge. This study employed a quasi-experimental design with data analysis conducted via MANCOVA by involving prior knowledge as a covariate. The analysis was performed using SPSS at a significance level of 0.05. The sample consisted of 135 seventh-grade students divided into three groups. Research instruments included a valid and reliable critical thinking skills test and a self-efficacy questionnaire. The analysis results indicated significant simultaneous differences among the groups. Further tests revealed that the DLLW group significantly outperformed both the DL and DI groups in both critical thinking skills and self-efficacy. These findings indicate that the integration of Discovery Learning with Liveworksheets is more effective than the comparison groups in improving students’ critical thinking skills and self-efficacy.Keyword: Discovery Learning, Liveworksheets, Critical Thinking, Self-Efficacy.